2007
DOI: 10.1080/00015458.2007.11680070
|View full text |Cite
|
Sign up to set email alerts
|

Life-threatening Biliary Complications after Percutaneous Nephro-Lithotomy: a Case Report

Abstract: Percutaneous nephrolithotomy is an option for the management of kidney stones. Rarely, life-threatening complications occur. A case of severe necrosis of the extrahepatic biliary tree after percutaneous neprolithotomy is hereby reported. A 55 years old woman underwent an emergency nephrectomy for bleeding the day after this procedure. One week later she developed an acute abdomen due to biliary peritonitis originating from necrosis of the choledochus and associated duodenal perforation. External biliary deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[ 1 ] Although rare with only a handful of reports, this is a potentially life-threatening complication, especially if not aggressively managed. [ 4 5 ] Gall bladder perforation leads to intraperitoneal accumulation of bile and, if not treated early, can cause sepsis that will need emergency laparotomy and cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Although rare with only a handful of reports, this is a potentially life-threatening complication, especially if not aggressively managed. [ 4 5 ] Gall bladder perforation leads to intraperitoneal accumulation of bile and, if not treated early, can cause sepsis that will need emergency laparotomy and cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with biliary tract injury during PCNL have been managed with cholecystectomy, either open[ 5 ] or laparoscopic. [ 1 ] Patil et al described a case wherein, after intraoperative aspiration of bile, the procedure was completed and the patient was managed conservatively with Ryles’ tube aspiration, antibiotics and intravenous fluids.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 8000 ultrasound-guided punctures, only 4 incidents were reported and none of them was with a renal puncture target ( 10 ). In review of the literature, there are few cases of biliary tract injury during isolated nephrostomy ( 6 ) or percutaneous nephrolithotomy ( 2 , 4 , 5 ), all of which have been managed by cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Till date, only six cases have been documented in literature [3]. This complication is life threatening if mismanaged [4]. Other organ injuries such as spleen, liver and colon have been documented, with gall bladder injuries being the least common.…”
Section: Discussionmentioning
confidence: 99%